Hodgkin Lymphoma in an Adolescent With Isolated Bone Marrow and Bone Involvement: A Case Report and a Review of the Literature. Issue 1 (January 2021) - Alkendi, Jalila; Renzi, Samuele; Manson, David; Abdelhaleem, Mohamed; Naqvi, Ahmed; Punnett, Angela
Abstract : Background: Primary presentation of Hodgkin lymphoma (HL) with bone and/or bone marrow involvement is a rare entity. Diagnostic criteria, treatment approaches, and follow-up strategies for these patients have not been standardized. Observation: We report a unique case of bone and bone marrow HL in an adolescent male without lymph node involvement. Conclusions: It is important to keep HL in the differential diagnosis of isolated and multifocal bone lesions. Evidence is needed to define the best management of these patients.